Casca de Astrocaryum aculeatum Meyer como substrato para produção de lacase por Pleurotus ostreatus LM 6226 para remoção de composto recalcitrante - Souza, Tayana Jessie Suwa Mesquita de (2018)
The enzyme laccase is used in industrial and biotechnological applications. Pleurotus ostreatus is a good laccase producer. They are, studies that investigate the reduction of costs of bioprocesses, including the strategy of using substrates for solid state bioprocessing. In the state of Amazonas, a bark of the fruit of the fruit, Astrocaryum aculeatum Meyer, is a widely produced time. The present work investigated the use of A. aculeatum Meyer fruit peel as a substrate for the production of glucose in solid state with P. ostreatus LM 6226. The bioprocess was carried out in Erlenmeyer flasks (125 mL) containing 15 g of culture medium (peels of tucumã, humidity of 70%). The screw was removed 10 plugs (5 mm) of mycelium removed from incubated Premium BDA plates (120 hours). Cultures were maintained at 25 ° C for 15 days. Univariate tests were the key to evaluate the factors: a) Growth temperature, b) Size of inoculum, c) % humidity, d) supplementation with wheat bran, e) presence of CuSO4 and f) Illumination regime. A kinetic was performed in climates, in the univariate ones. In additive, the influence of temperature, pH and laccase stability was investigated. Finally, the potential of the air removal technique (Reduction of Abs at 595 nm) of a solution of Remazol Brilliant Blue-R (RBBR) (200 mg/L) was investigated. The optimal conditions for laccase production using a fruit of the A. aculeatum as substrate were: temperature of 25 ºC, inoculum of 10 plugs per culture, 70% of humidity and incubation in environmental environment. The presence of wheat bran and copper sulphate are not produced in the production of the enzyme. The study of kinetics of laccase production demonstrated that no 10 years of bioprocess were observed as maximum activities of the enzyme. The quality and pH of great enzymes with pH 5 and indoor atmospheric radio between 25-50 ºC. Stability studies of the enzyme demonstrated laccases with residual residual> 85% when incubated for 24 at pH between 5-6 and residual activity> 75% when incubated for 70 min at temperatures between 25-30 °C. The RBBR blood solution removal assay had removal rates of up to 20% Abs (595 nm)/h. Keywords: Agroindustrial residue. Solid state bioprocess. Basidiomycetes. Enzyme. Dye.